2021
DOI: 10.1063/5.0039154
|View full text |Cite
|
Sign up to set email alerts
|

Pedestal magnetic turbulence measurements in ELMy H-mode DIII-D plasmas by Faraday-effect polarimetry

Abstract: Internal magnetic fluctuation measurements are utilized to identify turbulence associated with micro-tearing modes (MTM) in the DIII-D Edge-Localized-Mode (ELM)-y H-mode pedestal. Using a Faraday-effect polarimeter, magnetic turbulence (150–500 kHz) is directly observed with a typical line-averaged fluctuation amplitude of ∼0.8 G at peak frequency (250 kHz) and ∼15 G integrated over the spectrum from 150 to 500 kHz. Frequency, poloidal wavenumber, and propagation direction of the magnetic turbulence all serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 33 publications
6
33
0
Order By: Relevance
“…Recently on DIII-D, the implementation of a new Faraday-effect polarimetry measurement has allowed for the measurement of highfrequency magnetic turbulence in the pedestal region [29]. These results were shown to be consistent with high-n MTM fluctuations, helping to establish the experimental existence of MTMs [26,30]. On JET, detailed comparisons with gyrokinetic simulations showed that experimentally-observed frequency bands in magnetic fluctuations were consistent with expectations from MTMs and that MTM fluctuations produce experimentally-relevant transport [25].…”
Section: Introductionmentioning
confidence: 86%
“…Recently on DIII-D, the implementation of a new Faraday-effect polarimetry measurement has allowed for the measurement of highfrequency magnetic turbulence in the pedestal region [29]. These results were shown to be consistent with high-n MTM fluctuations, helping to establish the experimental existence of MTMs [26,30]. On JET, detailed comparisons with gyrokinetic simulations showed that experimentally-observed frequency bands in magnetic fluctuations were consistent with expectations from MTMs and that MTM fluctuations produce experimentally-relevant transport [25].…”
Section: Introductionmentioning
confidence: 86%
“…It should be mentioned that the power level from B is much lower than ñ for typical tokamak parameters. The relative magnetic fluctuation level B/B is from about 10 −4 to 10 −6 measured with typical tokamak parameter [4,16]. So the expected relative fluctuation level B/B 2 /| ñ/n| 2 ∼ 10 −2 -10 −5 [4,16,18,25].…”
Section: Jinst 17 C02025 4 Polarization Rejectormentioning
confidence: 90%
“…The relative magnetic fluctuation level B/B is from about 10 −4 to 10 −6 measured with typical tokamak parameter [4,16]. So the expected relative fluctuation level B/B 2 /| ñ/n| 2 ∼ 10 −2 -10 −5 [4,16,18,25]. As mentioned in reference [13,16], the scattered power from magnetic fluctuation P CPS ∝ ( B/B) 2 , and the scattered power from electron density fluctuation P DBS ∝ ( ñ/n) 2 .…”
Section: Jinst 17 C02025 4 Polarization Rejectormentioning
confidence: 99%
See 2 more Smart Citations